In God's garden : A daily devotional for women by women. - Stenbakken, Ardis Dick; Watts, Dorothy Eaton (Review and Herald, 1999)
You hold in your hands a treasury of courage and faithe, distilled from the experience of women who, like you, have faced the ups and downs of life and found strength in God's garden. Now their wisdom is yours. Nursed, doctors,wives, administrators, secretaries, and single moms share theirvictoreis in experiencing miracles, coping eith tragedy, cheering the downcast, dealing with a harsh boss, facing a scary trip, making new friends, finding missing keys, deaing with cancer, loving the unlovely, solving parenting problems, struggling with loneliness, crying for straying children, and learning to surrender.These servants of God found His peace as they sought His fellowship. And as you meet with them in garden , you too will find new strength, new courage for today, and now hope for tomorrow. Hard Back Review & Herald Publishing Association 1999 400 none